2016
DOI: 10.3168/jds.2015-10285
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of wheat bran and sugar beet pulp as sole supplements in high-forage diets emphasizes the potential of dairy cattle for human food supply

Abstract: Besides the widely discussed negative environmental effects of dairy production, such as greenhouse gas emissions, the feeding of large amounts of potentially human-edible feedstuffs to dairy cows is another important sustainability concern. The aim of this study was therefore to investigate the effects of a complete substitution of common cereal grains and pulses with a mixture of wheat bran and sugar beet pulp in a high-forage diet on cow performance, production efficiency, feed intake, and ruminating behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 31 publications
(63 reference statements)
5
40
2
1
Order By: Relevance
“…Demand to increase food production and to secure national food supply is growing (FAO, 2011;Eisler et al, 2014). Feeding agro-industrial by-products has recently been suggested as an efficient option to improve sustainability in terms of human-edible output, calculated as animal products minus potentially human-edible input of feedstuffs, in dairy production systems (Ertl et al, 2015b(Ertl et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demand to increase food production and to secure national food supply is growing (FAO, 2011;Eisler et al, 2014). Feeding agro-industrial by-products has recently been suggested as an efficient option to improve sustainability in terms of human-edible output, calculated as animal products minus potentially human-edible input of feedstuffs, in dairy production systems (Ertl et al, 2015b(Ertl et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has mainly focused on replacing single feed ingredients with agro-industrial by-products in diets to dairy cows. Apart from replacing pulses, an objective has often been to investigate and develop lower starch feeding strategies, to improve farm profitability and animal health in dairy production (e.g., Voelker and Allen, 2003;Dann et al, 2014;Ertl et al, 2016). Wheat bran and sugar beet pulp (SBP) are the most widely used nonforage fiber sources (NFFS) derived from agro-industries in Swedish ruminant production systems (Swedish Board of Agriculture, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study indicated that CS could be replaced with SBP up to 12% of dietary DM in the diets without adverse effects on the productivity of mid-lactating dairy cows during the summer (Naderi et al, 2016). Although there is evidence that BP could replace common cereal grains or CS in mid-lactation dairy cows without impairing performance (Ertl, Zebeli, Zollitsch, & Knaus, 2016;Voelker & Allen, 2003a), limited information is available on changes in feeding behaviour patterns as indicators of health.…”
mentioning
confidence: 99%
“…Ruminants are, therefore, able to produce edible protein of animal origin (milk and meat) from permanent meadows and pastures. They are enabling a net output of human edible protein and may contribute to meeting the human needs for food of animal origin (e.g., [83,84,85]). Kratli et al [86] pointed out that pastoralists are more efficient at producing food per unit area of dryland than other forms of agricultural land use under the same conditions.…”
Section: Methodsmentioning
confidence: 99%
“…They can be used as valuable sources of protein, minerals, and other nutrients depending on the source material and the chemical or physical processing, without causing any LF. In the future, more grain will be used for food and fuel and more co-products could be available for animal nutrition [21,85,97] or other purposes. Additional details about the nutritive value and utilization of co-products from the biofuel industry in animal nutrition were recently compiled by the FAO [95].…”
Section: Methodsmentioning
confidence: 99%